Intelligent real-time prediction for energy and sensing applications - Ramasamy, Arun Kumar (2022)
The advancements of science and technology has been rapid since the boom of the fourth industrial revolution that began arguable about a decade ago. As smart hardware and software began to be paired together over high speed transfer of information, the world of innovation witnessed the rise of Big Data and Machine Learning.